D-Xylitol Fermentative Production, Application and Commercialization - da Silva, Silvio Silvério; Chandel, Anuj Kumar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Commercially, D-xylitol is produced by chemical reactions that are tailored to the requirements of various sectors. However, due to the rising interest in sustainable development and ecologically benign practices, microbial transformation processes are generally preferred over the conventional chemical conversion process. The former have multiple advantages, including less chemical load on the environment, higher efficiency, and the ability to dilute multiple downstream transformation attempts while maintaining product yield and recovery.   This book aims to disseminate the most current advances in the biotechnological production of D-xylitol and its applications in medical and health care. It is a unique collection of 15 book chapters split into 5 sections and written by experts in their respective fields, who present critical insights into several topics, review current research, and discuss future progress in this area. This book also provides essential information on hemicellulose hydrolysis to recover D-xylose, detoxification of hemicellulose hydrolysates, and improved fermentation methods for increased D-xylitol production. The highlights of strain improvement to increase the D-xylitol titers and downstream recovery of D-xylitol are also discussed in several sections. The current applications of D-xylitol in medical and health care have been used to justify the cost incurred for setting up the demonstration plant for D-xylitol production in the market. Apart from researchers and post-graduate students in the field of microbial biotechnology, this book will assist those in the business community who deal with the economic analysis of bio-based products and their marketing.
Dilute Acid Hydrolysis of Agro-Residues: Implications on Xylose Recovery -- Deconstruction of Hemicellulose Fraction into Simple Sugars From Lignocellulosic Materials -- Molecular Mechanism of D-Xylitol Production in Yeasts: Focus on Molecular Transportation, Catabolite Sensing and Stress Response -- Microorganisms For Xylitol Production: Focus on Strain Improvement -- Statistical Optimization of Process Parameters for Xylitol Production -- Fermentation Strategies Explored for Xylitol Production -- Enzymatic Production of Xylitol -- Bioenergetic Balances for Xylitol Production from Different Lignocellulosic Materials --  An Assessment on Xylitol Recovery Methods -- Analytical Methods for Xylitol Quantification -- Medical Applications of Xylitol: An Appraisal -- Detoxification Strategies Applied to Lignocellulosic Hydrolysates for Improved Xylitol Production -- Key-Drivers Influencing the Large Scale Production of Xylitol --  Overview on Commercial Production of Xylitol, Economic  Analysis  and Market Trends.
Keywords: Microbiology; Microbial genetics; Microbial genomics; Microbiology; Applied Microbiology; Microbial Genetics and Genomics